Files de pierres dressées dans le sud de l'Éthiopie et au nord du Kenya - Roger Joussaume (OpenEdition, 2013)
Field researches of two American teams in the 1970s and 2000s have revealed several sites with lines of standing stones near Lake Turkana in the North of Kenya. The oldest could date from the beginning of the IIIth millennium BC, others have been dated from the second half of the Ist millennium BC. They were the work of a pastoral society who have known ceramic. In Sidamo, in the South of Ethiopia, the phallic steles of Gedeo and Sidama countries frequently form more or less long alignments, sometimes associated to a small elongated tumulus recovering a pit which seems to have been a grave. In Waheno, this pit contained a polished axe, some microlithes in obsidian and ceramic sherds. These sites could date from the Xth-XIIth centuries AD maybe related to the regional development of agriculture. South of Lake Chamo, in Ethiopia, the current inhabitants, Konso and Gewada, still raise stones on some occasions. The study of their social organization and their funeral customs allows to widen the debate on the functions of stone rows elsewhere in the world.